PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. POS INDONESIA DI KANTOR POS PUSAT GIANYAR - Dewa Ayu Diah Kharisma Dewi; I Wayan Widnyana; I Gusti Ngurah Bagus Gunadi (EMAS, 2022)
Employee performance has great potential to carry out company activities as well as possible so as to provide optimal output. This study aims to determine the effect of work motivation and job satisfaction on employee performance at PT. Pos Indonesia at the Gianyar Central Post Office. This research was conducted at PT. Pos Indonesia at the Gianyar Central Post Office, which is located at Jln. Abhimanyu No.4 Gianyar District, Gianyar Regency, Bali, with the object of research being work motivation, job satisfaction and employee performance. The population in this study were employees of PT. Pos Indonesia at the Gianyar Central Post Office, totaling 34 people. The sample from this study was determined by the saturated sample method, so the number of samples was 34 people. The data analysis technique used is multiple linear regression analysis. In addition, in this study, classical assumption tests were also carried out which included tests of normality, multicollinearity, and heteroscedasticity. The results of this study indicate that work motivation has a positive and significant effect on employee performance at PT. POS Indonesia at the Gianyar Central Post Office. job satisfaction has a positive and significant effect on employee performance at PT. POS Indonesia at the Gianyar Central Post Office.